Financial Performance Analysis of The Saving and Loan Cooperative - Fahriani, Dian; Zubaidah, Tantri Risda (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
This study aims to determine the financial performance of cooperatives in 2017-2019. The object of this research is the Analysis of the Financial Performance of the Savings and Loan Cooperative using the analysis method of the liquidity ratio, solvency and profitability. The data from this study were obtained from the results of company documents in the form of financial statements of the Financial Performance Savings and Loan Cooperative. The results of this study indicate that the liquidity ratio is measured using the Cash Ratio, 2017 to 2019 shows that financial performance is classified as in bad condition and Current ratio, in 2017 to 2019 shows that financial performance is in good condition. The solvency ratio measured using Debt to total Equity (DER) in 2017 to 2019 shows that financial performance is classified as in poor condition and Total debt to total asset ratio in 2017 to 2019 shows that financial performance is classified as in poor condition. not good. Profitability ratios measured using Return on Assets, 2017 to 2019 show that financial performance is in poor condition and Return on Equity (ROE) itself during 2017 to 2019 shows financial performance in unfavorable conditions according to 3 aspects of financial ratios for 2017-2019 declared unhealthy.